TEACHERS’ PERCEPTION OF THE EFFECT OF TEACHER CHARACTERISTICS ON THE INTERNAL EFFICIENCY OF PUBLIC SECONDARY SCHOOLS IN KERICHO COUNTY, KENYA - CHELULE, DANIEL KIPYEGON (KABARAK UNIVERSITY, 2016)
World initiatives in education such as Education for All (EFA) and the Millennium Development Goals (MDGs) have seen many governments make access to education central to their national development strategies mainly by reducing education costs. This has seen many governments invest heavily in education with Kenya allocating a third of her annual budget to education. However, despite this kind of investment, there is little empirical evidence to show that learners are benefitting commensurately. Studies suggest that the human resource plays a crucial role in school efficiency. This study sought to determine teachers‘ perception on the effect of teacher characteristics on the internal efficiency of public secondary schools. The Systems Approach and Production Function Theories were used to relate teacher characteristics (inputs) and internal efficiency of schools (output). Internal efficiency was measured in terms of students‘ academic outcomes at Kenya Certificate of Secondary Education. This study was conducted within Kericho County. It was based on five objectives which were to: establish the nature of internal efficiency; examine the effect of teacher qualification on internal efficiency; determine how teacher work experience affects internal efficiency; establish the effect of teacher workload on internal efficiency and to determine the influence of teacher turnover on internal efficiency of public secondary schools in Kericho County. The target population was 1318 teachers with the sample size being 298. Cluster sampling was used to sample three districts out of the five in the County. Simple random sampling was used to select teachers while the CDE, three DEOs and the ten Principals were selected using purposive sampling. Sampling of schools was based on school type such as national, county and district/day. Descriptive survey design was used to investigate the problem. Both quantitative and qualitative methods of data collection which included questionnaire, interview and document analysis were used. The questionnaire, interview guides, document checklist and audio recorder were used to collect and record data. Findings reveal that 23.5% of public secondary schools in Kericho County are efficient, 47.1% are moderately efficient while the remaining 29.4% are inefficient. Further, the study found a relationship between internal efficiency of schools and school type, whether national, county or district. The study showed that both teacher qualification and experience are perceived to positively affect internal efficiency while teacher workload and turnover are perceived as negative predictors of internal efficiency. This study concludes that teacher trainees joining pre-service teacher training meet minimum requirement in their teaching subjects and that practicing teachers pursue professional development courses. Recommendations are made to Teachers Service Commission to improve their terms of service to ensure retention of qualified and experienced teachers. Suggestions for further research on the effect of other variables other than teacher characteristics on internal efficiency of secondary schools are also made, among others.
FULL TEXT
Keywords: Teacher Characteristics, Internal Efficiency